1995
DOI: 10.1111/j.1464-5491.1995.tb02067.x
|View full text |Cite
|
Sign up to set email alerts
|

Aetiopathogenesis and Management of Impotence in Diabetic Males: Four Years Experience from a Combined Clinic

Abstract: The contribution of organic and psychogenic factors in the aetiopathogenesis of impotence was studied in a large number of diabetic males, to develop an algorithm for its management. We examined 110 consecutive patients who were referred to the Impotence Clinic of the Diabetes Centre. All patients were initially evaluated by a diabetologist and then underwent psychosexual assessment by a specialized psychiatrist. Patients with primarily organic disease were referred to a urologist for further management while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
7

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 23 publications
2
18
0
7
Order By: Relevance
“…Veves et al study also suggest that age is not a significant factor associated with SD. 18 BMI (p = 0.717) and WC (p = 0.138) were not significantly different between two groups in the present study. Veves et al also showed that BMI and WC were not significantly associated with ED.…”
supporting
confidence: 46%
See 1 more Smart Citation
“…Veves et al study also suggest that age is not a significant factor associated with SD. 18 BMI (p = 0.717) and WC (p = 0.138) were not significantly different between two groups in the present study. Veves et al also showed that BMI and WC were not significantly associated with ED.…”
supporting
confidence: 46%
“…Veves et al also showed that BMI and WC were not significantly associated with ED. 18 The association of obesity with other forms of SD not known.…”
mentioning
confidence: 99%
“…The results have demonstrated that 84% of our diabetic patients with ED had abnormal patterns suggesting an organic (peripheral) basis for their ED. These results, therefore, agree with those of Veves et al, 15 who found that diabetic ED is mainly organic in 89% of their patients. However, our results looked higher than that reported by other investigators who used NPT and found that about 70% of their diabetic patients had abnormal findings suggesting organic factors which contributed to their impotence.…”
Section: Discussionsupporting
confidence: 82%
“…Some of the early results of this work were presented at the Sixth Congress of the European Federation of Sexology, Limassol, Cyprus, June [16][17][18][19][20] 2002 and the Seventh Asian Congress of Sexology, Raffles City, Singapore, November [14][15][16][17] 2002.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…7 It is also quite prevalent in Europe and elsewhere. In a study we performed, we noted the work by Dr Rajfer who measured decreased nitric oxide in the penises of rats exposed to cigarette smoke, 8 and the relationship noted by Dr Shabsigh between cigarette smoking and vascular impotence.…”
Section: Pathophysiologymentioning
confidence: 99%